The religious-political ideology of houthis’ rebellion in Yemen : theoretical perspective of the divine right to rule - Sarhan, Mugahed S.; Mohd Irwan Syazli Saidin; Zarina Othman (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article examines the religious-political ideology of the Houthi movement in Yemen. In particular, it explores the political objectives and historical roots of the Houthis’ rebellion that was initiated in 2004 and continued into 2009 through six rounds of wars, which were called Sa’dah wars. The Houthis implemented a military coup in 2014 against Mansour Hadi’s government and seized state institutions which led to Yemen’s current civil war. A catastrophic battle also erupted when the Saudi-led military coalition decided to intervene in the conflict in 2015, with the aim of restoring the legitimacy of the previous regime as well as defeating the Houthis insurgency. Despite numerous studies on the issues relating to civil war in Yemen, there is no adequate study on the perspective of Houthis’ religious-political ideology. This research is qualitative using in-depth interviews with seven experts and observers of the Yemeni war. This article analyses major reasons for the historical rebellion and the ongoing catastrophic war in Yemen, based on the Houthis’ religious-political ideology. The findings of this article inform that the current conflict in Yemen is rooted in historical circumstances which gave rise to a heavy responsibility or burden on the Houthis, whereby according to the theory of the divine right to rule, the Houthis and their ancestors, the Hashemites claim the monopoly of regional (present day Yemen) power. Thus, this theory has been considered as one of the key dynamics of the outbreak and the continuation of the current war in Yemen. It is very likely that the trend of increased Houthis’ rebellion will continue for the next few years in Yemen due to the movement’s firm aim of power struggle, based on their religious-political ideology of the ‘divine right to rule’.